The use of Learning Strategy in Reading of Reflective Learners - Nabila Ayu Nisa (CV. Tripe Konsultan, 2022)
The goal of this study was to see if there was a significant difference between the three types of reflective learners' reading learning strategies. The participants were 35 Senior High School students in Bandar Lampung, who were in the 12th grade. The Matching Familiar Figure Test (MFFT) was used to categorize students into reflectivity/impulsivity, and the Language Learning Approach Questionnaire (LLSQ) was administered to determine students' learning strategy preferences. The data was analyzed using One Way ANOVA with a significance level of 0.05. The findings revealed that reflective learners' reading strategies differed significantly from those utilized by non-reflective learners. According to the finding, Reflective learners used more metacognitive reading methods that were related to their own prior experience and knowledge.